2016
DOI: 10.7453/gahmj.2015.104
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine Use in the US Adult Low Back Pain Population

Abstract: Background:Many people suffering from low back pain (LBP) have found conventional medical treatments to be ineffective for managing their LBP and are increasingly turning to complementary and alternative medicine (CAM) to find pain relief. A comprehensive picture of CAM use in the LBP population, including all of the most commonly used modalities, is needed.Study Objective:To examine prevalence and perceived benefit of CAM use within the US LBP population by limiting vs nonlimiting LBP and to evaluate the odds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 20 publications
4
49
0
2
Order By: Relevance
“…CIH recipients were younger and more likely to be female, which is consistent with findings in outpatient settings, 26,32 and in other inpatient populations such as cardiology. 33 It appears that CIH might be appealing to inpatients with certain demographic factors (e.g., middle-aged and female), or it is possible that those patients are more likely to receive CIH referrals from clinical providers.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…CIH recipients were younger and more likely to be female, which is consistent with findings in outpatient settings, 26,32 and in other inpatient populations such as cardiology. 33 It appears that CIH might be appealing to inpatients with certain demographic factors (e.g., middle-aged and female), or it is possible that those patients are more likely to receive CIH referrals from clinical providers.…”
Section: Discussionsupporting
confidence: 87%
“…Our study found that 14.2% of 8,095 inpatients with mechanical LBP in one Midwestern hospital received some form of CIH. As expected, the utilization of CIH for mechanical LBP within a hospital setting (14.2%) is lower than in the general LBP population (42.2% 26 or 47.6% 27 ). While the general LBP population estimates provide context, they are not comparable to the inpatient estimates for several reasons.…”
Section: Discussionsupporting
confidence: 71%
“…12 Acupuncture plays an important role in Traditional East Asian Medicine (TEAM) treatment of pain. 13 Several systematic reviews on the effectiveness and safety of acupuncture treatment in lower back pain patients have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Amerika'da sırt ağrısı yaşayan hastaların %41.2'si TİSU yöntemlerini kullanmaktadır [9]. Türkiye'de de ağrı nedeniyle TİSU kullanım sıklığı benzerdir [10].…”
Section: Introductionunclassified